Mimic of cellulitis: Primary cutaneous B cell lymphoma - Leg type - Sathish Pai; Kanthilatha Pai; Shrutakeerthi Shenoi; Shastry BA (Our Dermatology Online, 2015)
Primary cutaneous B-cell lymphoma, leg type, is an uncommon and aggressive subtype of Primary cutaneous B cell lymphoma that is recently updated by the World Health Organization-European Organization for Research and Treatment of Cancer classification of cutaneous lymphomas. We present a case of an 80-year-old woman who presented with redness and swelling mimicking cellulitis of her right leg, along with few skin colored nodules. Skin biopsy revealed pathology consistent with this entity. The patient was treated with systemic chemotherapy, but expired while on treatment secondary to sepsis.